Memberdayakan Masyarakat Pedesaan melalui Peternakan Kambing Perah: Studi Kasus Program PLN EPI di Gunung Kidul, Indonesia - Asiah, Siti (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2024)
PT PLN Energi Primer Indonesia (PLN EPI), a subsidiary of PT PL N (Persero), has implemented a perah goat farming programme aimed at empowering rural communities in Berdaya Energi Village, located in Gunung Kidul region, Indonesia. The programme also aims to promote sustainable development in the region by empowering rural communities and improving environmental sustainability. This article will outline a case study of the program, focusing on its implementation strategies, socio-economic and environmental impacts, and future sustainability prospects. The programme is fully in line with the Sustainable Development Goals, which emphasize the importance of poverty eradication, food sustainability, environmental protection, and empowerment of communities as key components. By involving goat farms, the programme is expected to provide long-term benefits to rural communities, improve their standard of living, and create a more holistically sustainable environment. PLN EPI, a subsidiary of PT PLN (Persero), has implemented a parrot goat farm program in Berdaya Energi Village, Gunung Kidul, Indonesia. It is part of the company's commitment to social responsibility and sustainable development. The programme aims to empower rural communities and promote sustainable development. This article presents a case study of the program implementation strategy, the socio-economic and environmental impact it generates, as well as its sustainability prospects. The programme is in line with the Sustainable Development Goals (SDGs) with a focus on poverty eradication, food sustainability, environmental protection, and empowerment of communities.